TraV: A Genome Context Sensitive Transcriptome Browser - Dietrich, Sascha; Wiegand, Sandra; Liesegang, Heiko (PloS one, 2014)
Next-generation sequencing (NGS) technologies like Illumina and ABI Solid enable the investigation of transcriptional activities of genomes. While read mapping tools have been continually improved to enable the processing of the increasing number of reads generated by NGS technologies, analysis and visualization tools are struggling with the amount of data they are presented with. Current tools are capable of handling at most two to three datasets simultaneously before they are limited by available memory or due to processing overhead. In order to process fifteen transcriptome sequencing experiments of Bacillus licheniformis DSM13 obtained in a previous study, we developed TraV, a RNA-Seq analysis and visualization tool. The analytical methods are designed for prokaryotic RNA-seq experiments. TraV calculates single nucleotide activities from the mapping information to visualize and analyze multiple transcriptome sequencing experiments. The use of nucleotide activities instead of single read mapping information is highly memory efficient without incurring a processing overhead. TraV is available at http://appmibio.uni-goettingen.de/index.php?sec=serv.